(untitled) (International Journal of Nursing Education, 2019)
“An experimental study to assess the effectiveness of foot and hand massage on reducing pain among postnatal mothers who had undergone caesarean section at postnatal ward of Sharda Hospital, Greater Noida, U.P” Purpose of the study: The purpose of the study was to determine the effectiveness of Foot and Hand Massage on reducing post caesarean pain among the postnatal mother. Methodology: The study has adopted a Quasi Experimental with Randomized pre-test post-test control group design was used and then sample were assigned randomly to experimental group and control group respectively. Sixty postnatal mothers, thirty in experimental group and thirty in control group were selected as the subject of the study. Both group were selected consecutively and randomly assigned to either experimental or control group. Sociodemographic Profile, Numeric Pain scale were used as tool for data collection. Results: Majority of (70%) mothers was having obstetrical score in the experimental group and (60%) in the control group had obstetrical score as multigravida. Most of the mothers (63.3%) were having 1st postnatal in experimental group and (53.3%) in control group had 2nd postnatal day. The homogeneity was checked in both the group and it was found that there was no homogeneity in term of Age, Obstetrical score, Postnatal day, Type of Anesthesia, History of previous Caesarean, Family income, Education status, Type of family, Previous information regarding massage only postnatal day found to be associated. The Analysis of effectiveness of Foot and Hand Massage for reducing pain was checked by independent “t” test. It showed that from baseline to after 20 minutes of Foot and Hand Massage mean pain score in Experimental group were (3.4) and mean pain score in Control group were (5.46).On Comparison of mean difference pain score in experimental group were (4.68) and in Control group were (2.46) at 0.05% level of significance. This indicates that the reduction in pain score was not by chance but because of the intervention. On Comparison of mean pain score difference in experimental group is relatively high compare to control group at 0.05% level of significance. Conclusion: This study showed that Foot and Hand Massage are more effective along with hospital routine treatment than among the postnatal mothers. Foot and Hand Massage can be used in reducing post Caesarean pain. The Foot and Hand Massage can be offered to every mother who had undergone caesarean section as treatment until and unless they have not any postpartum complications.